The long QT syndrome in South Africa - Brink, P.A.; Corfield, V.A. (SA Heart Journal, 2017)
The long QT syndromes (LQTS) are Mendelian inherited conditions where syncope and sudden death are due to precipitous occurrence of polymorphic ventricular tachycardia. In South Africa a number of white, some coloured and some Asian individuals have been identified but, interestingly, not a single black person and neither has it been reported from Africa. With over 400 known causal-mutations, mostly in cardiac ion channel-genes, it is unlikely to be absent in African populations. LQTS is notorious for going undiagnosed or misdiagnosed, perhaps even more so in Africa. Amongst persons of Afrikaner descent the KCNQ1 A341V-mutation represents a founder effect. The availability of 170 living individuals sharing the same mutation has made it possible to study factors modifying risk. A blunted autonomic response has been shown to decrease risk of attacks.